Human resistin is a systemic immune-derived proinflammatory cytokine targeting both leukocytes and adipocytes. - Ivan Nagaev; Maria Bokarewa; Andrej Tarkowski; Ulf Smith (PLoS ONE, 2006)
The characteristics of human resistin (RETN) are unclear and controversial despite intensive adipose-focused research. Its transcriptional and functional similarity with the murine myeloid-specific and CCAAT/enhancer binding protein epsilon (Cebpe)-dependent gene, resistin-like gamma (Retnlg), is unexplored. We examined the human CEBPE-regulatory pathway by unbiased reference and custom gene expression assays. Real-time RT-PCR analysis demonstrated lack of both the transcriptional factor CEBPE and RETN expression in adipose and muscle cells. In contrast, primary myelocytic samples revealed a concerted CEBPE-RETN transcription that was significantly elevated in inflammatory synoviocytes relative to intact peripheral blood mononuclear cells (PBMC). Mouse Cebpe and Retnlg were predictably expressed in macrophages, whereas Retn was abundant in adipocytes. Quite the opposite, a low and inconsistent RETN transcription was seen in some human white adipose tissue (WAT) biopsies without any relationship to body mass index, insulin sensitivity, or fat depot. However, in these cases, RETN was co-detected with CEBPE and the leukocyte-specific marker, EMR1, indicating the presence of inflammatory cells and their possible resistin-mediated effect on adipocytes. Indeed, addition of human resistin to WAT in culture induced, like in PBMC, the inflammatory cytokines IL6, IL8 and TNF. Importantly, the expression of the adipose-specific markers CEBPA, FABP4 and SLC2A4 was unchanged, while the expected inhibitory effect was seen with TNF. Both cytokines increased the mRNA level of CCL2 and MMP3, which may further promote inflammation in WAT. Thus, the myeloid-restricted nature of CEBPE precludes the expression of RETN in human adipocytes which, however, are targeted by this innate immune-derived proinflammatory cytokine.